Divine Emanation As Cosmic Origin: Ibn Sînâ and His Critics - Syamsuddin Arif (Universitas Darussalam Gontor, 2012)
The question of cosmic beginning has always attracted considerable attention from serious thinkers past and present. Among many contesting theories that have emerged, that of emanation was appropriated by Muslim philosophers like Ibn Sînâ in order to reconcile the Aristotelian doctrine of the eternity of matter with the teaching of al-Qur’ân on the One Creator-God. According to this theory, the universe, which comprises a multitude of entities, is generated from a transcendent Being, the One, that is unitary, through the medium of a hierarchy of immaterial substances. While the ultimate source is undiminished, the beings which are emanated are progressively less perfect as they are further removed from the first principle. The process is conceived as being atemporal and often compared to the efflux of light from a luminous body, or to water flowing from a spring. This metaphysical theory has enabled Ibn Sînâ to solve the vexed problem: given an eternally existing world and one eternally existing God, how can the two necessarily co-exist without having the perfect, simple unity of God destroyed by contact with the multiplicity of material things? The following essay delineates and evaluates both Ibn Sînâ’s arguments as well as the counter-arguments of his critics.